2023
DOI: 10.3390/medicina59122069
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety Impact on Anesthetic and Analgesic Use

Hanaa Baagil,
Hamzah Baagil,
Mark Ulrich Gerbershagen

Abstract: Anxiety is a complex emotional state that can arise from the anticipation of a threatening event, and preoperative anxiety is a common experience among adult patients undergoing surgery. In adult patients, the incidence of preoperative anxiety varies widely across different surgical groups, and it can result in a variety of psychophysiological responses and problems. Despite its negative impact, preoperative anxiety often receives insufficient attention in clinical practice. To improve pain management strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that preoperative education significantly reduces perioperative anxiety and postoperative pain [ 31 , 32 , 33 ]. Along with education, anxiolytic interventions such as pharmacological therapies (benzodiazepines, sympatholytics, anti-epileptics, and antidepressants) and other alternative therapies (aromatherapy, music therapy, and acupuncture) should also be considered [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have demonstrated that preoperative education significantly reduces perioperative anxiety and postoperative pain [ 31 , 32 , 33 ]. Along with education, anxiolytic interventions such as pharmacological therapies (benzodiazepines, sympatholytics, anti-epileptics, and antidepressants) and other alternative therapies (aromatherapy, music therapy, and acupuncture) should also be considered [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The STAI questionnaire is considered the gold standard tool for measuring state and trait anxieties owing to its well-established validity and reliability [10,21]. The STAI-KYZ is a translated version of the STAI-Y (Spielberger, 1983), which has been rebalanced by a number of positive and negative questions.…”
Section: Anxiety-measuring Toolsmentioning
confidence: 99%
See 2 more Smart Citations